2020
DOI: 10.1002/ps.5872
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional identification of a Chilo suppressalis‐inducible promoter of rice gene, OsHPL2

Abstract: BACKGROUNDPromoters play a key role in driving insect‐resistant genes during breeding of transgenic plants. In current transgenic procedures for breeding rice resistance to striped stem borer (Chilo suppressalis Walker, SSB), the constitutive promoter is used to drive the insect‐resistant gene. To reduce the burden of constitutive promoters on plant growth, isolation and identification of insect‐inducible promoters are particularly important. However, few promoters are induced specifically by insect feeding.RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 114 publications
1
5
0
Order By: Relevance
“…The inducing ability of OsAOS1 promoter is close to that of the CaMV35S promoter even at 24 h after insect feeding (Figure ). We further investigated that increasing the number of repeats of the regulatory region ( P1R1 ) could significantly enhance the promoter induction function (Figure 5d), indicating that insect inducible promoters have a functional superposition effect, and this phenomenon was also found in our previous research (Li et al, 2020). Erenow, this phenomenon was only found in some bacteria, fungal inducible promoters, and a few tissue‐specific promoters (Bai et al, 2019; Rytter et al, 2014; Sohoni et al, 2014).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The inducing ability of OsAOS1 promoter is close to that of the CaMV35S promoter even at 24 h after insect feeding (Figure ). We further investigated that increasing the number of repeats of the regulatory region ( P1R1 ) could significantly enhance the promoter induction function (Figure 5d), indicating that insect inducible promoters have a functional superposition effect, and this phenomenon was also found in our previous research (Li et al, 2020). Erenow, this phenomenon was only found in some bacteria, fungal inducible promoters, and a few tissue‐specific promoters (Bai et al, 2019; Rytter et al, 2014; Sohoni et al, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…However, research on insect‐inducible promoters is lagging far behind. So far, only a few insect‐inducible promoters have been reported (Hua et al, 2007; Li, Wang, et al, 2020; Siddique et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Godard et al (2007) showed that the potato proteinase inhibitor II (PinII) promoter was able to drive the woundand insect-inducible GUS expression in Picea glauca (white spruce), Arabidopsis, or tobacco. Li et al (2020) observed that the rice hydroperoxide lyase (OsHPL2) gene promoter was significantly upregulated after herbivory of C. suppressalis, but not after feeding of Nilaparvata lugens, mechanical wounding, abscisic acid, jasmonic acid or salicylic acid treatments. Despite the advantages of inducible promoters over constitutive promoters that have been widely used in the genetic engineering of many plants, the trade-offs between inducibility and strength should be considered for practical biotechnological application.…”
Section: Insect-inducible Promotersmentioning
confidence: 99%
“…As early as 2001, researchers found that introducing the spider insecticidal gene, SpI , into rice enhanced its resistance to the SSB and rice leaf roller [ 107 ]. Li et al [ 129 ] found that the promoter of the rice hydroperoxide lyase gene, OsHPL2 , was specifically induced by the SSB, and then optimized to connect with Cry1C and transformed it into rice. Compared with the rice transformed with Cry1C alone, it showed a stronger level of resistance to the SSB.…”
Section: Transgenic Strategiesmentioning
confidence: 99%